2006
DOI: 10.1039/b606132j
|View full text |Cite
|
Sign up to set email alerts
|

Development of a method for bacteria and virus recovery from heating, ventilation, and air conditioning (HVAC) filters

Abstract: The aim of the work presented here is to study the effectiveness of building air handling units (AHUs) in serving as high volume sampling devices for airborne bacteria and viruses. An HVAC test facility constructed according to ASHRAE Standard 52.2-1999 was used for the controlled loading of HVAC filter media with aerosolized bacteria and virus. Nonpathogenic Bacillus subtilis var. niger was chosen as a surrogate for Bacillus anthracis. Three animal viruses; transmissible gastroenteritis virus (TGEV), avian pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 25 publications
0
63
0
Order By: Relevance
“…For example, particulate cake can serve as a protection for microorganisms or as a support for the adsorption of organic matter, which is used as a substrate (Kuehn et al 1991;Li et al 2010). AHU management improves energy saving and indoor air quality criteria by optimizing several factors: filtration efficiency, comfort of occupants, energy consumption, frequency of changing filters, and efficiency/cost balance (Kemp et al 2001;M€ oritz et al 2001;Farnsworth et al 2006). Operation of AHUs can influence IAQ, for example, when ventilation is stopped or reduced during nights, weekends, or holidays.…”
Section: Introductionmentioning
confidence: 99%
“…For example, particulate cake can serve as a protection for microorganisms or as a support for the adsorption of organic matter, which is used as a substrate (Kuehn et al 1991;Li et al 2010). AHU management improves energy saving and indoor air quality criteria by optimizing several factors: filtration efficiency, comfort of occupants, energy consumption, frequency of changing filters, and efficiency/cost balance (Kemp et al 2001;M€ oritz et al 2001;Farnsworth et al 2006). Operation of AHUs can influence IAQ, for example, when ventilation is stopped or reduced during nights, weekends, or holidays.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that the sampling device could detect a low microorganism concentration with low power requirements due to the absence of pressure drop inside the EPSS (Han et al, 2010). Farnsworth et al (2006) conducted a study to evaluate the effectiveness of building air handling units and determining whether they can serve as high volume samplers for airborne bacteria and viruses. To test this, they nebulized and injected aerosols into a test facility upstream of a MERV 14 filter.…”
Section: Air Samplingmentioning
confidence: 99%
“…This has been accomplished by immersing small filters or portions of filters in a solution of a Tween surfactant in water and agitating by one of the several methods for a suitable time [16,18,19,25,27,28]. Forms of agitation evaluated have included manual shaking [18,28], mechanical shaking [18,19,25], blending [18,27], vortexing [16,19], and ultrasonic vibration [16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [16] discovered that ultrasonic vibration after vortexing improved recovery beyond vortexing by itself. Bacteria in the eluate can be analyzed using culture-based methods [16,19,25,27,28] or molecular techniques [9].…”
Section: Introductionmentioning
confidence: 99%